Intermittent oxygen inhalation increase maximal workload and maximal heart rate in elite athletes - Lindholm, P.; Boberg, O.; Frånberg, O.; Larsson, A.; Gullstrand, L. (The FASEB Journal, 2013)
Recent studies on pulmonary shunt during exercise suggest that oxygen per se could close shunts and thus increase arterial PO2. We hypothesized that a small increase in intrapulmonary PO2 (5-10kPa) would suffice to get performance enhancing effect of oxygen. We also hypothesized that intermittent addition of 10-20l/min of oxygen to inspired air could yield this increase without using premixed gas in athletes ventilating 150-250 l/min.